Labor Union Renewal in Argentina: Democratic Revitalization from the Base - Montes Cato, Juan Sebastian (2011)
Despite the persecution of labor leaders and activists during the dictatorship of the 1970s and 1980s and the co-optation of the union leadership in the 1990s, in the past few years Argentine labor unions have regained some of the leadership role they lost when they became strategic allies of the government, moderating their wage demands and supporting the government in disputes with other strong social actors. The new landscape created by Néstor Kirchner’s taking office in 2003 provided a favorable context for a revitalization of unions grounded in principles of union democracy. The experience of the subway workers of Buenos Aires, which is paradigmatic for the depth of the changes in internal practices, their persistence over time, and the strong connection between the form of organization and the results achieved, contributes to an understanding of this revitalization. The involvement of members in formulating and implementing policies produces a program more representative of their demands and allows them to acquire experience, skills, knowledge, self-confidence, and a feeling of solidarity that make their organizations stronger for the struggle with capital. Thus union democracy is not an obstacle to but a prerequisite for increasing union power.